Transformation in Strategic Management Approaches: From Linear Planning to Agile and Digital Approaches - Seyyed Sina Ahrar (Eximia, 2025)
This review article explores the shift in strategic management from traditional linear planning models to increasingly prevalent agile and digital methodologies driven by rapid technological advancements, globalization, and growing business complexity. The study synthesizes current literature on the use of agile approaches in many industries, emphasizing how these approaches promote adaptability in strategic management. The primary analysis focuses on juxtaposing traditional, linear, and agile approaches in strategical management, utilizing case studies and expert insights to elucidate the advantages and challenges. However, the review also recognizes possible limitations, including the details involved in transitioning to agile systems and the scalability of this methodology within large organizations. Through a detailed analysis of these challenges, we offer insights into effective implementation strategies and best practices for successful transformation. The paper concludes by discussing the future trajectory of strategic management in a digital-first world, emphasizing the paramount importance of adaptability, and the continuous evolution of agile and digital approaches to maintain a competitive edge.